On the Origin of the Harmonic Term in Noncommutative Quantum Field Theory - Goursac, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
The harmonic term in the scalar field theory on the Moyal space removes the UV-IR mixing, so that the theory is renormalizable to all orders. In this paper, we review the three principal interpretations of this harmonic term: the Langmann-Szabo duality, the superalgebraic approach and the noncommutative scalar curvature interpretation. Then, we show some deep relationship between these interpretations.